Model Regresi Rating Curve Stasiun Awlr Jurug antara Tinggi Muka Air dan Debit pada Sungai Bengawan Solo - Supadi, Supadi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
River of Bengawan Solo have been attached instrument of water discharge appliance which it’s location in downstream of Colo Weir precisely at ± 200 m upstream of Jurug bridge and the  AWRL Post was located most pate of upstream and founded in 1969 and also represent permanent building called AWLR (Automatic Water Level Recorder), so that shall have known the result of discharge curve which have been made from  year to year. The Making of Rating curve in Post of Jurug at Bengawan Solo river represent model of rating curve discharge Result of a measurement between water level surface and discharge are highly varied since 1977 - 2000 (34 datas) and the result cause by change of river cross section influenced by agradation and degradation of river bed. So need to analyse of rating curve study in Jurug post before and after the construction  of Wonogiri Dam. Discharge curve varied to be need observe and measurement in the long time and continuous measurement data from year to year and also performed a measurement charge by continuous and get result of discharge which different each other. The Rating Curve usefulness are obvious that is to know discharge of stream passing at the location from existence of change time to time.Permalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/2094[How to cite: Supadi, 2006, Model Regresi Rating Curve Stasiun Awlr Jurug antara Tinggi Muka Air dan Debit  pada Sungai Bengawan Solo, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 2, pp. 179-188]